Desenvolvimento de sistema de revestimento anticorrosivo nanoestruturado e antibiofouling baseado em Fusion Bonded Epoxy para aplicação em tubulações metálicas utilizadas na extração de petróleo - Patricia Alves Saliba (2017)
Corrosion in pipelines intended for offshore oil extraction significantly reduces its lifetime, increasing costs, and even more serious, can cause catastrophic environmental accidents. These pipes are also subjected, to a lesser extent, to corrosion caused by macro and microorganisms, in particular due to the phenomenon of biofouling. Given this scenario, the development of protective coatings for steel pipes is of extreme importance. In this work, an anti-corrosion system based on fusion bonded epoxy coating (FBE) reinforced with 3aminopropyltriethoxysilane (3-APTES) modified silica nanoparticles was developed and deposited on 3-APTES chemically modified API 5L X42 steel solid support. Preliminary properties of the antifouling chitosan agent incorporated FBE coating were also evaluated. The systems were extensively characterized in relation to their chemical, thermal and mechanical properties. In addition, performance tests were performed against cathodic delamination, and against the biofouling model, using bovine serum albumin (BSA) protein. It was found that the modification of the steel with 3-APTES promoted interfacial reactions with the FBE coating, resulting in greater adhesion of the FBE coating to the metal support. The curing process of the nanoparticle reinforced coating promoted the formation of homogeneous nanocomposites through the development of interfacial reactions between its constituent phases, promoting a better integration between the nanoparticles and the epoxy matrix, and increasing the thermal stability of the coating. The steel/coating system developed had its performance improved against the cathodic delamination mechanism potentially reflecting what occurs in marine pipelines immersed in the marine environment. It was observed that the incorporation of the polysaccharide chitosan in the FBE coating promoted a bsa protein adsorption decreasing, used as model macromolecule, being an indication of a possible improvement of antifouling activity of the modified FBE coating. These results suggest the promising potential for the use of the new FBE based nanocomposite under severe oil extraction conditions and extend the application of this coating to reduce the biofouling phenomenon present in marine environments